1995
DOI: 10.1007/bf02577835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipids on soy protein isolate solubility

Abstract: Reduced-lipid soy protein isolate (SPI), prepared from soy flour treated so that most of the polar lipids have been removed, exhibited an increase in protein solubility of 50% over that of the control SP1 prepared from hexane-defatted flour. Adding lipids from a commercial SPI during processing of reduced-lipid SPI decreased SPI solubility by 46%. The 19% decreased solubility caused by the lipids (primarily phospholipids) was largely recovered by treating the protein with a reducing agent (2-mercaptoethanol). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 24 publications
(15 reference statements)
3
55
1
Order By: Relevance
“…Factors affecting the decrease of soybean proteins solubility are numerous, and they cause complex processes that result in degradation, denaturation and polymerisation of proteins. Boatright and Hattiarchchy (1995), point out that protein solubility is affected by internal factors-hydrophilic and hydrophobic characteristics of protein molecules, their size and charge, as well as the interaction with other kernel components, and also by external factors-temperature, pH value, type and ionic strength of different salts [17]. Hager, (1984), determined that extrusion decreases the content of soluble proteins of soybean kernel from 60-66% to 25-30% [18].…”
Section: Resultsmentioning
confidence: 99%
“…Factors affecting the decrease of soybean proteins solubility are numerous, and they cause complex processes that result in degradation, denaturation and polymerisation of proteins. Boatright and Hattiarchchy (1995), point out that protein solubility is affected by internal factors-hydrophilic and hydrophobic characteristics of protein molecules, their size and charge, as well as the interaction with other kernel components, and also by external factors-temperature, pH value, type and ionic strength of different salts [17]. Hager, (1984), determined that extrusion decreases the content of soluble proteins of soybean kernel from 60-66% to 25-30% [18].…”
Section: Resultsmentioning
confidence: 99%
“…This was most probably caused by the aggregation of protein molecules since the fat content of soy protein isolates is usually very low (less than 0.5%) and did not show significant difference (data are not shown here). However, the presence of residual lipids in defatted soy flours which are not extractable by non-polar solvent did cause problems in protein properties, as suggested by Boatright and Hettiarachchy (1995). A strong beany off-fla- b Relative contents of 11S calculated as the sum of acid polypeptides and basic peptides and 7S as the sum of a, a 0 and b subunits.…”
Section: Physicochemical Characterization Of Soy Proteinsmentioning
confidence: 96%
“…Some researches proposed that 7S/11S interaction, especially the preferential association between the basic polypeptides of 11S and the b-subunit of 7S leading to the formation of soluble aggregates could be a key factor determining the gelation of soy proteins (German, Damodaran, & Kinsella, 1982;Utzumi, Damodaran, & Kinsella, 1984). Boatright and Hettiarachchy (1995) reported that lipid components could reduce protein solubility of soy protein isolates, suggesting that factors other than protein structure should also be examined. It is well known in soy protein processing circle that the difference in starting material (defatted soy flour) would influence functional properties but there are few systematic work to study their relationships; variation in 11S/7S ratio and degree of denaturation is generally considered as the determining variables.…”
Section: Introductionmentioning
confidence: 98%
“…Laboratory SPI was prepared by dispersing hexane-defatted soybean flour (obtained from Protein Technologies International Inc., St. Louis, MO) in water (1 part flour to 10 parts water) at 22°C followed by additions of 1 N sodium hydroxide, as needed, until a pH of 9 was achieved and maintained for 15 min (21). After centrifugation at 1500 × g for 10 min, the supernatant was adjusted to a pH of 4.5 with 1 N HCl to precipitate proteins.…”
Section: Chemicalsmentioning
confidence: 99%